Expressive Modulation of the Cyp7a1 and Ibat Protein by Cholesterol and its Contribution to the Maintenance of the Normal Cholesterolemia in Mouse - ATTAKPA, S. EUGÈNE; Djibril, Naguibou; Ahokpè, Mélanie; SEZAN, ALPHONSE (My University, 2012)
The aim of our study is to prove the existence of a very coordinated system of regulation be-tween the route of excretion of taurocholic acid and cholesterol. We proceed to follow up phys-iologically animals, with no differences in water and food consumptions between the control group and the group of 5% diet of cholesterol. On the other hand dieresis has increased in mice with 5% diet of cholesterol. Cholesterol induced in the liver the transcribed rate of Cholesterol 7α-hydroxylaze (CYP7A1), limiting enzyme of bile acids synthesis. What’s more, expression of CYP7A1 encoding gene is induced in mice with 5% diet of cholesterol. Also we noticed an in-crease of distribution and wealth expression related to the RNA and CYP7A1 in the liver report-ed by Northern Blotting. According to ileum role in intestinal re-absorption of bile acids, our interest was focused on the ileac transportation: the standard expression of Ileal Bile Acid Transporter (IBAT) has strongly reduced; in mice with rich diet of cholesterol the Western Blot-ting of proteins has quantitatively reduced. IBAT’s oppression can be explained by the diminu-tion of the ileac transportation of taurocholic acid (TCA).It results an increase of fecal flight of TCA in mice with a rich diet of cholesterol.
Keywords: Bile acids; cholesterol; taurocholic acid; CYP7A1; IBAT; Mouse